Rationalization of anisotropic mechanical properties of Al-6061 fabricated using ultrasonic additive manufacturing. (15th September 2016) - Sridharan, Niyanth; Gussev, Maxim; Seibert, Rachel; Parish, Chad; Norfolk, Mark; Terrani, Kurt; Babu, Sudarsanam Suresh
Abstract: Ultrasonic additive manufacturing (UAM) is a solid-state process, which uses ultrasonic vibrations at 20 kHz along with mechanized tape layering and intermittent milling operation, to build fully functional three-dimensional parts. In the literature, UAM builds made with low power (1.5 kW) exhibited poor tensile properties when loaded along the Z-direction, i.e., normal to the interfaces. This reduction in properties is often attributed to the lack of bonding at the interfaces. The generality of this conclusion is evaluated further in 6061 aluminum alloy builds made with very high power UAM (9 kW). Tensile deformation behavior along X and Z directions were evaluated with small-scale in-situ mechanical testing equipped with high-resolution digital image correlation, as well as, multi-scale characterization of builds. Interestingly, even with complete metallurgical bonding across the interfaces without any discernable voids, poor Z-direction properties were observed. This reduction is correlated to coalescence of pre-existing shear bands at interfaces into micro voids, leading to strain localization and spontaneous failure on tensile loading. Graphical abstract: